Step
*
1
of Lemma
assert-bag-all
1. T : Type
2. eq : EqDecider(T)
3. p : T ⟶ 𝔹
4. bs : bag(T)
5. ∀x:T. (x ↓∈ bs 
⇒ (↑p[x]))
⊢ bag-all(x.p[x];bs) = tt
BY
{ xxx(MoveToConcl (-1) THEN UseWitness ⌜λz.Ax⌝⋅)xxx }
1
1. T : Type
2. eq : EqDecider(T)
3. p : T ⟶ 𝔹
4. bs : bag(T)
⊢ λz.Ax ∈ (∀x:T. (x ↓∈ bs 
⇒ (↑p[x]))) 
⇒ bag-all(x.p[x];bs) = tt
Latex:
Latex:
1.  T  :  Type
2.  eq  :  EqDecider(T)
3.  p  :  T  {}\mrightarrow{}  \mBbbB{}
4.  bs  :  bag(T)
5.  \mforall{}x:T.  (x  \mdownarrow{}\mmember{}  bs  {}\mRightarrow{}  (\muparrow{}p[x]))
\mvdash{}  bag-all(x.p[x];bs)  =  tt
By
Latex:
xxx(MoveToConcl  (-1)  THEN  UseWitness  \mkleeneopen{}\mlambda{}z.Ax\mkleeneclose{}\mcdot{})xxx
Home
Index